Europe under multi-year droughts: how severe was the 2014–2018 drought period?. (8th March 2021) - Moravec, Vojtěch; Markonis, Yannis; Rakovec, Oldrich; Svoboda, Miroslav; Trnka, Miroslav; Kumar, Rohini; Hanel, Martin
Abstract: The recent dry and warm years in Europe are often assessed as extreme in terms of socio-economic and environmental losses. However, the impact of a drought is a function of its duration. This fact needs to be considered in the evaluation of a drought. In this study, we use a hydrological model to analyze the 2018 European drought, an event that significantly affected vegetation. We show that the severity of the soil moisture drought is high in Central Europe and Mediterranean, but it does not reach the levels observed in the first half of the 20th century. Nevertheless, we demonstrate that when the multi-year 2014–2018 period is considered, its soil moisture drought severity is exceptional in a 253 year period, especially for Central Europe. While single-year droughts can be sustained by ecosystems like forests, the repeated stress exposure of such multi-year droughts may have significant impacts on their functioning. This is already evident in some regions of Central Europe, e.g. in the Czech Republic, Germany, and Poland.